The meanings and methods of improving the technical and tactical training of free-style wrestlers - Abdullaev, Altai; Абдуллаєв, Алтай Карам-Огли; Абдуллаев, Алтай Карам-Оглы; Rebar, I (My University, 2020)
At present, the level of development of wrestling in the world is characterized by two main trends ‒ the mutual penetration of knowledge and technologies for building training of the leading wrestling schools and constant changes in the rules of competitions in order to increase the entertainment and popularity of wrestling in the world. In this regard, the search for innovative approaches to improving technical and tactical actions is an urgent aspect of the modern system of training wrestlers at the stage of specialized basic training. Based on the data of the analysis of competitive fights of high-class wrestlers, the expediency of improving the technical and tactical actions of qualified wrestlers is substantiated. When improving the technical and tactical actions of qualified freestyle wrestlers, the basic elements of technique and tactics of wrestling were taken into account: the spatial orientation of the wrestlers; the background of the fight: the implementation of the capture; transition from one grip to another; release from grips by blocks and stops; maneuvering; embossing; unbalancing in order to create a favorable situation; implementation of a favorable situation by a technique; the position of the wrestler after the attacking action, as well as the features of the competitive activity at the present stage. The developed means and methods aimed at improving the technical and tactical actions of qualified freestyle wrestlers have shown their effectiveness in the process of the training process. unbalancing in order to create a favorable situation; implementation of a favorable situation by a technique; the position of the wrestler after the attacking action, as well as the features of competitive activity at the present stage. The developed means and methods aimed at improving the technical and tactical actions of qualified freestyle wrestlers have shown their effectiveness in the process of the training process. unbalancing in order to create a favorable situation; implementation of a favorable situation by a technique; the position of the wrestler after the attacking action, as well as the features of competitive activity at the present stage. The developed means and methods aimed at improving the technical and tactical actions of qualified freestyle wrestlers have shown their effectiveness in the process of the training process.
Keywords: wrestling; free-style wrestlers; sport; physical education